Donor-derived fatal hyperinfection strongyloidiasis in renal transplant recipient - Ana Cipriano; Rita Dias; Ricardo Marinho; Sofia Correia; Virgínia Lopes; Teresa Cardoso; Irene Aragão (IDCases, 2020)
Strongyloides stercoralis is a nematode, endemic in tropical and subtropical areas. Strongyloidiasis has been reported in recipients of hematopoietic stem cells, kidney, liver, heart, intestine, and pancreas, eventually presenting as disseminated strongyloidiasis and hyperinfection syndrome (SHS) which is associated with high mortality. We report one case of a recent renal transplant recipient, who presented with gastrointestinal and respiratory symptoms, evolving into shock. The identification of Strongyloides stercoralis in the bronchoalveolar lavage (BAL) lead us to the diagnosis of SHS. Treatment with subcutaneous ivermectin was started, however the patient did not survive. Retrospective serum donor analysis allowed us to identify the donor as the source of infection. Keywords: Donor-derived infection, Strongyloides stercoralis, Strongyloides hyperinfection syndrome, Subcutaneus irvemectin, Kidney transplantation